2016
DOI: 10.1111/echo.13421
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular rotational mechanics in infants with hypoxic ischemic encephalopathy and preterm infants at 36 weeks postmenstrual age: A comparison with healthy term controls

Abstract: Infants with HIE have reduced rotational mechanics. Preterm infants at 36 weeks PMA have comparable measurements of twist to term infants. This is achieved by predominant basal rather than apical rotation. Infants with CLD have increased apical rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
(69 reference statements)
3
26
0
Order By: Relevance
“…The LVEF remained stable, ranging between 46% and 66% during the study period and the semi‐automated method produced comparable LVEF with less measurement variability. The LVEF in the early post‐transitional period and at 36 weeks PMA reported in this study is similar to the LVEF in previous reports 22–25 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The LVEF remained stable, ranging between 46% and 66% during the study period and the semi‐automated method produced comparable LVEF with less measurement variability. The LVEF in the early post‐transitional period and at 36 weeks PMA reported in this study is similar to the LVEF in previous reports 22–25 …”
Section: Discussionsupporting
confidence: 91%
“…This study reports longitudinal biplane LVEF in very preterm infants during the neonatal intensive care period and feasibility of speckle tracking software for semi‐automatic determination of LVEF. In spite of immaturity of myocardial architecture, the biplane LVEF in preterm infants observed in this study was similar to LVEF previously reported in term infants, which indicates that the efficiency of the LV pump to handle the physiologic preload is well established in preterm infants during the early postnatal period 14,22–25 . The LVEF remained stable, ranging between 46% and 66% during the study period and the semi‐automated method produced comparable LVEF with less measurement variability.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…There are a number of factors related to calcium delivery and use in the neonatal myocardium which impair contractile ability. The sarcoplasmic reticulum (SR), which senses and triggers calcium-induced calcium release (CICR) in order to potentiate contraction is immature, as well as the T-tubules which invaginate into the myocyte to bring L-type calcium channels into closer contact with the SR ryanodine receptors (Ikonnikov and Yelle, 2013;Breatnach et al, 2017). There is evidence that these factors, alongside altered calcium handling, lead to generation of less force during contraction (Wiegerinck et al, 2009).…”
Section: The Mechanics Of Cardiac Output: Contractilitymentioning
confidence: 99%